Soil Compaction: An Agronomic and Environmental view (Research, Society and Development, 2022)
The objective of this research was to investigate the agronomic and environmental understanding of civil society and people linked to the area of ​​agricultural sciences about the questions involving the problems caused by soil compaction. The methodology used was based on the use of an electronic form from the Google Forms platform, published on social media and shared by third parties from 12:00 pm on February 22, 2022 and ended at 12:00 pm on February 28, 2022. Altogether 213 responses were obtained, and their respondents were concentrated in the Northeast region. It is observed that the majority of respondents were aged between 18 and 18 years old, working in the agricultural sciences, and knew how to say what soil compaction is. They present an understanding of its definition, origin and problems. In addition to knowing the ways to avoid and recover the soil. Therefore, it is concluded that compaction is a problem that directly affects most agricultural areas, due to incorrect soil management practices and it is necessary for agricultural science professionals to seek new alternatives for the prevention and recovery of densely populated lands.